Development Of Aesthetic Theory in Byelorussia - Salejevas, Vadimas (Problemos, 1984)
Having traced back the historic development of Byelorussian aesthetic thought, the author gives his utmost attention to the analysis of the state of aesthetic theory during the last two decades. Three main trends stand out in modem Byelorussian aesthetic theory: (a) historical research into development of artistic culture and aesthetic thought; (b) theoretical analysis of the problems of nature, genesis, functions, and perception of art as well as the problems of artistic and aesthetic education, and (c) the “University trend” whose representatives are engaged in studying the contents of aesthetic categories.